Wolbachia infection decreased the resistance of Drosophila to lead. - Ling Wang; Chun Zhou; Zhen He; Zheng-Guang Wang; Jia-Lin Wang; Yu-Feng Wang (PLoS ONE, 2012)
BACKGROUND: The heavy metal lead has been shown to be associated with a genotoxic risk. Drosophila melanogaster is a model organism commonly utilized in genetic toxicology testing. The endosymbionts--Wolbachia are now very common in both wild populations and laboratory stocks of Drosophila. Wolbachia may induce resistance to pathogenic viruses, filarial nematodes and Plasmodium in fruit fly and mosquito hosts. However the effect of Wolbachia infection on the resistance of their hosts to heavy metal is unknown. METHODOLOGY/PRINCIPAL FINDINGS: Manipulating the lead content in the diet of Drosophila melanogaster, we found that lead consumption had no different effects on developmental time between Wolbachia-infected (Dmel wMel) and -uninfected (Dmel T) flies. While in Pb-contaminated medium, significantly reduced amount of pupae and adults of Dmel wMel were emerged, and Dmel wMel adults had significantly shorter longevity than that of Dmel T flies. Lead infusion in diet resulted in significantly decreased superoxide dismutase (SOD) activity in Dmel T flies (P<0.05), but not in Dmel wMel flies. Correspondingly, lead cultures induced a 10.8 fold increase in malonaldehyde (MDA) contents in Dmel T larvae (P<0.05). While in Dmel wMel larvae, it resulted in only a 1.3 fold increase. By quantitative RT-PCR, we showed that lead infused medium caused significantly increased expression level of relish and CecA2 genes in Dmel T flies (P<0.01). Lead cultures did not change dramatically the expression of these genes in Dmel wMel flies. CONCLUSIONS/SIGNIFICANCE: These results suggest that Wolbachia infection decreased the resistance of Drosophila to lead likely by limiting the production of peroxides resulted from lead, thus being unable to activate the immunological pathway in the host to prevent them from lead damage. This represents a novel Wolbachia-host interaction and provides information that researchers working on Drosophila toxicology should take in consideration the presence of Wolbachia in the stocks they are analyzing.